The 1st International Electronic Conference on Algorithms 2021
DOI: 10.3390/ioca2021-10909
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Deep Learning Approach for COVID-19 Diagnosis via CT and X-ray Medical Images

Abstract: The COVID-19 pandemic has been a global health problem since December 2019. To date, the total number of confirmed cases, recoveries, and deaths has exponentially increased on a daily basis worldwide. In this paper, a hybrid deep learning approach is proposed to directly classify the COVID-19 disease from both chest X-ray (CXR) and CT images. Two AI-based deep learning models, namely ResNet50 and EfficientNetB0, are adopted and trained using both chest X-ray and CT images. The public datasets, consisting of 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is the combination of X-ray and CT datasets. The accuracy, specificity, recall and f1-score values of the proposed method with hybrid chest X-ray and COVID CT dataset are more than the other ResNet50 and EfficientNetB0 [ 7 ] with the hybrid dataset.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…It is the combination of X-ray and CT datasets. The accuracy, specificity, recall and f1-score values of the proposed method with hybrid chest X-ray and COVID CT dataset are more than the other ResNet50 and EfficientNetB0 [ 7 ] with the hybrid dataset.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation was achieved via the testing sets. We experimentally fine-tuned the AI models to achieve the best accuracy based on the trail-based error approach [ 57 , 58 ]. All of our experiments are conducted utilizing the various optimization functions available in ADAM, RMSP, and SGDM.…”
Section: Methodsmentioning
confidence: 99%
“…We will guide our future work according to the conclusions drawn from the preceding analysis, which indicated that: i) the amalgamation of data from diverse sources yields more impactful and practical solutions [19]; ii) the application of feature extraction and selection techniques is crucial in ML [20]; and iii) enhanced accuracy in predictions is achieved through the utilization of hybrid ML algorithms [21]- [23]. We will implement these insights by following the steps outlined below, as illustrated in Figure 2:  Collect the data sets: we will focus on gathering data related to the disorders examined, encompassing diabetes, cancer, thyroid issues, liver conditions, kidney diseases, Alzheimer's, hypertension, and cardiovascular ailments.…”
Section: Challenge and Potential Future Workmentioning
confidence: 99%